The Effect of Motivation and Discipline on the Performance of Teachers and Employees at Smk Negeri 1 Langowan, Minahasa Regency - Mautang, Artistic Thean; Masengi, Evi; Mokad, Jetty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study was to determine the extent of the influence of motivation and discipline on the performance of teachers and employees at SMK Negeri 1 Langowan, Minahasa Regency. The research method uses a quantitative approach using a cross sectional study research design, namely data collection and research conducted at the same time. The data collection technique was done with a questionnaire. The results showed that there is a significant relationship between motivation and employee discipline at SMK Negeri 1 Langowan. The contribution of motivation (X1) and discipline (X2) together to performance (Y) is 34.6%.